Insights in the global genetics and gut microbiome of black soldier fly, Hermetia illucens: implications for animal feed safety control - Khamis, F.M.; Ombura, F.L.; Akutse, K.S.; Subramanian, S.; Mohamed, S.A.; Fiaboe, K.K.; Saijuntha, W.; Loon, Jelle J. van; Dicke, M.; Dubois, T.; Ekesi, S.; Tanga, C.M. (Frontiers Media, 2020)
The utilization of the black soldier fly (BSF) Hermetia illucens L. for recycling organic waste into high-quality protein and fat biomass for animal feeds has gained momentum worldwide. However, information on the genetic diversity and environmental implications on safety of the larvae is limited. This study delineates genetic variability and unravels gut microbiome complex of wild-collected and domesticated BSF populations from six continents using mitochondrial COI gene and 16S metagenomics. All sequences generated from the study linked to H. illucens accessions KM967419.1, FJ794355.1, FJ794361.1, FJ794367.1, KC192965.1, and KY817115.1 from GenBank. Phylogenetic analyses of the sequences generated from the study and rooted by GenBank accessions of Hermetia albitarsis Fabricius and Hermetia sexmaculata Macquart separated all samples into three branches, with H. illucens and H. sexmaculata being closely related. Genetic distances between H. illucens samples from the study and GenBank accessions of H. illucens ranged between 0.0091 and 0.0407 while H. sexmaculata and H. albitarsis samples clearly separated from all H. illucens by distances of 0.1745 and 0.1903, respectively. Genetic distance matrix was used to generate a principal coordinate plot that further confirmed the phylogenetic clustering. Haplotype network map demonstrated that Australia, United States 1 (Rhode Island), United States 2 (Colorado), Kenya, and China shared a haplotype, while Uganda shared a haplotype with GenBank accession KC192965 BSF from United States. All other samples analyzed had individual haplotypes. Out of 481,695 reads analyzed from 16S metagenomics, four bacterial families (Enterobactereaceae, Dysgonomonadaceae, Wohlfahrtiimonadaceae, and Enterococcaceae) were most abundant in the BSF samples. Alpha-diversity, as assessed by Shannon index, showed that the Kenyan and Thailand populations had the highest and lowest microbe diversity, respectively; while microbial diversity assessed through Bray Curtis distance showed United States 3 (Maysville) and Netherlands populations to be the most dissimilar. Our findings on genetic diversity revealed slight phylogeographic variation between BSF populations across the globe. The 16S data depicted larval gut bacterial families with economically important genera that might pose health risks to both animals and humans. This study recommends pre-treatment of feedstocks and postharvest measures of the harvested BSF larvae to minimize risk of pathogen contamination along the insect-based feed value chain.